Legal Implications of the Notary Honour Council's Approval on the Summoning of Notaries by Law Enforcers - ARDANARI, Ni Made Novia Surya; SENASTRI, Ni Made Jaya; I Made Pria Dharsana (Journal of Political And Legal Sovereignty, 2025)
Purpose:The approval of the Notary Honour Council (MKN) has legal implications in the summoning of notaries. However, several cases have raised legal debates regarding the authority of MKN, as well as the potential for conflicts of interest.  Therefore, it is necessary to investigate: how is the legal regulation of MKN approval when summoning a notary by law enforcement and what are the legal implications of MKN approval on the status of notaries in the process of investigation and investigation. The objectives of this research are general and specific.Methodology:This research is also classified as a type of normative legal research. This research uses a statutory approach, concept approach, and case approach. The data used in this research is secondary data consisting of primary, secondary, and tertiary legal materials and supported by interview data from sources.Findings:Based on the results of the research, it is known that: there are regulations that become the juridical basis for summoning notaries by law enforcers, namely Law Number 30 of 2004 concerning Notary Position which was last amended in Law Number 2 of 2014 and Permenkumham Number 17 of 2021. Based on these regulations, the procedures and mechanisms in requesting/requesting MKN approval are: First, submission of a request by law enforcement officials to MKN regarding the collection of photocopies of the Minute of Deed and summoning Notaries. Second, examination and decision making by MKN.Implication:In addition, the results also show that approval or rejection from MKN has legal implications in the law enforcement process. If the Examining Council gives approval, then the notary is obliged to: provide a photocopy of the deed minutes and/or the required letter to law enforcement accompanied by the minutes of delivery and must fulfil the summons. However, if MKN refuses, then law enforcement cannot make efforts to take a photocopy of the Minute of Deed and cannot make efforts to summon the notary.